Myocardial transcription of inflammatory and remodeling markers in cats with hypertrophic cardiomyopathy and systemic diseases associated with an inflammatory phenotype. (May 2021) - Fonfara, Sonja; Kitz, Sarah; Monteith, Gabrielle; Hahn, Shelley; Kipar, Anja
Abstract: Feline hypertrophic cardiomyopathy (HCM) is characterized by macrophage-driven myocardial remodeling processes in a pro-inflammatory environment. To further investigate the mechanisms behind these processes, the myocardial transcription of cytokines and remodeling enzymes was comparatively assessed in cats with HCM and cats without cardiac diseases. Sixty-seven cats were included, 17 cats with HCM (including 5 with atrial thrombus; AT), and 50 cats without cardiac diseases. The latter comprised 10 control cats (no cardiac or relevant systemic disease), 34 cats with diseases suspected to be associated with a systemic inflammatory state of which 18 suffered from feline infectious peritonitis (FIP), and 6 cats with multicentric lymphoma. Samples from atria, ventricular free walls and interventricular septum were examined using quantitative reverse transcriptase PCR. The overall highest myocardial marker transcriptions were observed in cats with multicentric lymphoma, FIP and HCM, followed by diseases likely associated with a systemic inflammatory state, and control cats. Inflammatory marker transcription predominated in the myocardium of cats with systemic inflammatory diseases, whereas in HCM the transcription of remodeling enzymes prevailed. Sex significantly influenced the myocardial transcription of several remodeling enzymes. These results suggest a versatile myocardial response depending on the disease and illustrates the relevance of sex for the cardiac response to cardiac and systemic disease in cats. A systemic inflammatory state appears to elicit an inflammatory phenotype in the myocardium, whereas in HCM, the myocardium mediates its own remodeling. In HCM, the identified markers might be involved in the ongoing remodeling processes causing structural and functional changes. Highlights: Inflammatory systemic diseases elicit an inflammatory phenotype in the myocardium. Inflammation appears not be involved in cardiac remodeling in advanced feline HCM. Remodeling markers MMP-2, MMP-3, TIMP-3 are involved in HCM in male cats. In HCM, myocardial mRNA levels differ between cats with and without atrial thrombus. Sex influences the cardiac response to cardiac and systemic disease in cats.